2021
DOI: 10.1093/plphys/kiab046
|View full text |Cite
|
Sign up to set email alerts
|

Hexose transporter CsSWEET7a in cucumber mediates phloem unloading in companion cells for fruit development

Abstract: In the fleshy fruit of cucumbers (Cucumis sativus L.), the phloem flow is unloaded via an apoplasmic pathway, which requires protein carriers to export sugars derived from stachyose and raffinose into the apoplasm. However, transporter(s) involved in this process remain unidentified. Here, we report that a hexose transporter, CsSWEET7a (Sugar Will Eventually be Exported Transporter 7a), was highly expressed in cucumber sink tissues and localized to the plasma membrane in companion cells of the phloem. Its expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 71 publications
4
32
0
Order By: Relevance
“…The presence of PD in the SE-CC connection has been reported as evidence of symplasmic unloading in tomatoes [ 53 ], kiwi [ 54 ], grape berries [ 55 ] and jujube [ 25 ] ( Table 1 ). In other fruits, such as apples [ 49 ], strawberries [ 56 ], cucumbers [ 57 , 58 , 59 ] and watermelons [ 60 ], apoplastic phloem delivery predominates at all developmental stages ( Table 1 ). Phloem unloading can switch from the symplasmic to the apoplastic pathway during fruit development according to physiological demands and environmental conditions [ 11 , 48 ] ( Figure 1 ).…”
Section: Phloem Unloading Pathways In Developing Fruits: a Role For Pdmentioning
confidence: 99%
“…The presence of PD in the SE-CC connection has been reported as evidence of symplasmic unloading in tomatoes [ 53 ], kiwi [ 54 ], grape berries [ 55 ] and jujube [ 25 ] ( Table 1 ). In other fruits, such as apples [ 49 ], strawberries [ 56 ], cucumbers [ 57 , 58 , 59 ] and watermelons [ 60 ], apoplastic phloem delivery predominates at all developmental stages ( Table 1 ). Phloem unloading can switch from the symplasmic to the apoplastic pathway during fruit development according to physiological demands and environmental conditions [ 11 , 48 ] ( Figure 1 ).…”
Section: Phloem Unloading Pathways In Developing Fruits: a Role For Pdmentioning
confidence: 99%
“…So far, all plant SWEETs with a measured Km, e.g. AtSWEET1 (Chen et al, 2010), AtSWEET12 (Chen et al,2012), AtSWEET17 (Guo et al, 2014), SlSWEET1a (Ho et al, 2019) and CsSWEET7a (Li et al, 2021), have been found to function as low-affinity glucose or sucrose transporters, ranging from ~10 to ~120 mM. It is not unusual to observe that a SWEET transports different sugars but with different efficiency and Kms (Chen et al, 2010, Kuanyshev et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…So far, all plant SWEETs with measured Km, e.g. AtSWEET1 (Chen et al, 2010), AtSWEET12 (Chen et al,2012), AtSWEET17 (Guo et al, 2014), SlSWEET1a (Ho et al, 2019) and CsSWEET7a (Li et al, 2021), have been found to function as low-affinity sugar transporters, ranging from ~10 to ~120 mM. AtSWEET5/VEX, belonging to SWEET family Clade II that primarily transports hexose (Chen et al, 2010;Eom et al, 2015), is strongly expressed in the pollen vegetative cell (Engel et al, 2005), but no other details have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucrose transporter (SUT) and monosaccharide transporters [e.g., sugar transport protein (STP)] were reported to function at the latter step ( Büttner, 2010 ; Borghi and Fernie, 2017 ), while a sugar exporter (functioning at the first step) has not been reported in flowers. Cucumber Sugar Will Eventually be Exported Transporter 7a (SWEET7a) is known to localize the companion cells in fruit vascular bundles and to export hexose to the apoplasmic space to stimulate sugar unloading in fruit ( Li et al, 2021 ). In Arabidopsis pollen, AtSWEET8 and AtSWEET13 are involved in pollen maturation, and an aborted silique phenotype was observed in sweet8 single mutant ( Guan et al, 2008 ), while this phenotype was more severe in sweet8;13 double mutant ( Sun et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%